Exploring Parents’ and Teachers’ Perspectives about School-Based Sexuality Education in a Multicultural Context: A Case Study in Mauritius - Wajiihah Banu Shah Emambokus; Brinda Oogarah-Pratap (Educational Process: International Journal)
The importance of school-based Sexuality Education (SE) programs is widely recognized. Effective implementation of such programs require that due consideration be given to sociocultural factors that can constitute enablers and potential barriers. Numerous research studies on these aspects have been conducted in developed countries. However, there is a lack of such studies in developing countries, especially studies involving school-aged adolescents from a multicultural context and from socioeconomically deprived areas. Therefore, this small-scale study uses a qualitative approach to research conducted in Mauritius, a developing country with a significantly multicultural population, and where SE is addressed in a fragmented manner within the school curriculum, despite changes noted in the sexual behaviors of the country’s adolescents. The aim of the study was to explore parents’ and teachers’ perspectives of sociocultural factors that can act as enabling factors or potential barriers. The study involved semi-structured interviews of two parents and two teachers selected through purposive sampling at a secondary school which has students from diverse cultural backgrounds and mostly from socioeconomically deprived areas. Analysis of the interview transcripts revealed that the enabling factors were perceived as the importance of school-based SE by parents and teachers, contribution of external organizations, and a two-way communication process with adolescents. The potential barriers were perceived as a resistance from some teachers and students, the gender of the parent, and religion. Generation gap and ICT were found to be both enablers and barriers. The findings have implications for the design and implementation of school-based SE within a multicultural context and pave the way for similar studies on a larger scale.